Whole Genome Sequencing of a Non-O1/O139-Group Vibrio cholerae Isolated from a Patient with a Bloodstream Infection - Wang S; Jin S; Zhu X; Li Y; Pan X (Infection and Drug Resistance)
Sipei Wang,1 Shanshan Jin,1 Xiangjin Zhu,1 Yuan Li,1 Xinling Pan2 1Department of Clinical Laboratory, Wenzhou Medical University Affiliated Dongyang Hospital, Dongyang, Zhejiang, People’s Republic of China; 2Department of Biomedical Sciences Laboratory, Wenzhou Medical University Affiliated Dongyang Hospital, Dongyang, Zhejiang, People’s Republic of ChinaCorrespondence: Xinling Pan, Department of Biomedical Sciences Laboratory, Wenzhou Medical University Affiliated Dongyang Hospital, No. 60 Wuning West Road, Dongyang, Zhejiang Province, People’s Republic of China, 322100, Email panfengyuwuzu@163.comBackground: Diarrhea caused by non-O1/O139-group V. cholerae (NOVC) tends to be mild and can be readily overlooked. In this report, a NOVC strain designated XXM was isolated from the blood of a 68-year-old male undergoing surgical treatment for a bile duct malignancy in October 2023.Methods: XXM was identified through a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Virulence genes were detected using a V. cholerae ctxA/ctxB virulence gene dual real-time fluorescent PCR kit. AST-GN13 and AST-GN334 cards were used to test the resistance against 16 antibiotics with a Vitek2 compact system. The genomic and phylogenetic characteristics of XXM were established through whole genome sequencing (WGS).Results: Serum agglutination tests revealed the isolate to be a non-O1/non-O139 strain. The strain was sensitive to all 16 tested antibiotics and did not carry the ctxA/ctxB gene. MLST analyses identified the XXM strain as ST1538. WGS analyses identified 8 classes of virulence genes with different functions. A total of 3.541 bacterial genes, including 3.482 from V. cholerae, were annoted using the Non-Redundant Protein Sequence (NR) database. Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses annotated 32 genes including 17 key proteins involved in the V. cholerae biofilm pathway. Comparative analyses using the Pathogen Host Interactions Database (PHI) identified the YbeY gene. Evolutionary genealogy of genes: Non-supervised Orthologous Groups (eggNOG) was used to annotate 3280 genes in 21 categories. Phylogenetic analyses revealed that strain XXM was closely related to V. cholerae strain Man9.Conclusion: The XXM carries multiple virulence genes, and this genomic analysis of the XXM in comparison with other NOVC strains provides important information for an improved understanding of the pathogenicity of NOVC in clinical samples.Keywords: Vibrio cholerae, non-O1/O139-group, whole genome sequencing, bloodstream infection, molecular characterization